Improving the efficiency of thermoelectric generator using perturb and observe MPPT algorithm - Nurul Izzah Izzati Zaihan; Tengku Norliza Tengku Mohamad; Fakroul Ridzuan Hashim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Maximum Power Point Tracking (MPPT) is a crucial strategy for maximizing energy extraction from Thermoelectric Generators (TEGs). Various MPPT techniques, such as Interval Type 2 Fuzzy Logic Controller (IT2FLC), Extremum Seeking Control (ESC), and Perturb and Observe (P&O), have been developed to achieve optimal power output from TEG systems. Among these methods, the P&O technique stands out due to its ease of implementation and control scheme, cost-effectiveness, and high output power. This paper proposes a design that integrates TEG arrays, boost converters, and the P&O algorithm to optimize power extraction from TEG systems. The performance of the system utilizing the P&O based MPPT technique is compared to the system without MPPT under the same operating conditions, highlighting the significant of MPPT in enhancing TEG efficiency. The results demonstrate that the P&O algorithm effective increases the efficiency of MPPT in TEG systems. This study was conducted using the MATLAB/Simulink environment.